Effect of Alendronic Acid on Fracture Healing: A Multicenter Randomized Placebo‐Controlled Trial. (7th March 2019) - Duckworth, Andrew D; McQueen, Margaret M; Tuck, Christopher E; Tobias, Jonathan H; Wilkinson, Jeremy Mark; Biant, Leela C; Pulford, Elizabeth Claire; Aldridge, Stephen; Edwards, Claire; Roberts, Chris P; Ramachandran, Manoj; McAndrew, Andrew Richard; et al.
ABSTRACT: There is a concern that bisphosphonates may impair fracture healing because of their inhibitory effects on bone turnover. Here we evaluated the effects of early bisphosphonate therapy on fracture healing and functional outcome following a fracture of the distal radius. The fracture and bisphosphonates (FAB) trial was a double‐blind, randomized, placebo‐controlled trial involving 15 trauma centers in the United Kingdom. We enrolled 421 bisphosphonate‐naive patients aged ≥50 years with a radiographically confirmed fracture of the distal radius and randomized them in a 1:1 ratio to receive alendronic acid 70 mg once weekly ( n = 215) or placebo ( n = 206) within 14 days of the fracture. The primary outcome measure was the proportion of fractures that had radiologically united at 4 weeks as assessed by an observer, blinded to treatment allocation. Secondary outcomes included the Disabilities of the Arm Shoulder and Hand (DASH) questionnaire, range of wrist movement and grip strength, pain and analgesia requirements, and the rate of malunion. The mean ± SD age of participants was 63 ± 8.5 years and 362 (86%) were female. At 4 weeks, 48 of 202 (23.8%) fractures had united in the alendronic acid group compared with 52 of 187 (27.8%) in the placebo group (observed absolute proportion difference 4.0%; 95% CI, –4.7% to 12.8%; p = 0.36). The absolute proportion difference between groups based on imputed data was 4.5% (95% CI, –4.7% to 13.8%; p = 0.30). There was no significant difference in the proportion of fractures that had united at any other time point and no differences in the DASH score, pain at the fracture site, grip strength, or any other clinical outcome. We conclude that among patients aged 50 years and above with a distal radius fracture, early administration of alendronic acid does not adversely affect fracture union or clinical outcome. These findings suggest bisphosphonate therapy can be safely commenced early after fracture if clinically indicated. © 2019 American Society for Bone and Mineral Research.